Large Omphalocele presenting as ventral hernia in a 12-year-old child: case report - Noureen , Sadaf; Noor Ul Haq, Mahwish; Zafar, Zuha; Javed, Muhammad Habib; Umm-e-Rubab; Fatima, Nimra (Journal of the Pakistan Medical Association, 2026)
A 12-year-old girl presented to the department of paediatric surgery of Mayo Hospital Lahore on March 31, 2021, with a large omphalocele that healed as ventral hernia. Primary closure of the defect was done. This case highlights the importance of public awareness regarding congenital anomalies, early detection, and timely management to reduce childhood mortality and lifelong disability because delays in treatment may result in one of these disability and poor quality of life. Key words: Ventral hernia, Large omphalocele, Abdominal wall defect.